Influence of supragingival biofilm control and smoking habit on Interleukin-1β concentration - Sabrina Carvalho GOMES; Carolina Coradini ABASCAL; Alex Nogueira HAAS; Patricia Daniela Melchiors ANGST; Rui Vicente OPPERMANN; Rosemary Adriana Chierici MARCANTONIO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This investigation compared gingival crevicular fluid (GCF) interleukin-1β (IL-1β) concentrations in periodontitis patients subjected to a strict supragingival biofilm control (Supra) for 6 months. Never-smokers (23) and smokers (n = 20; 19.6 ± 11.8 cigarettes/day) moderate-to-severe chronic periodontitis patients underwent a 6 months period of supragingival control with weekly recall visits. Periodontal probing depth (PPD), bleeding on probing (BOP) and GCF samples (from different PPD category sites: 3-5 mm and 6-10 mm) were obtained at the baseline, 30, and 180 days. IL-1β was assessed by enzyme-linked immunosorbent assay. Generalized estimating equations were used to fit prediction models of IL-1β changes, considering the dependence between the examinations, and using only data from experimental sites. Overall IL-1β concentrations decreased from 3.2 pg/µL to 1.9 pg/µL. Higher baseline IL-1β concentrations were associated with higher baseline PPD values in both groups. There were no differences in IL-1β concentrations between never-smokers and smokers over time for any PPD category. Higher baseline PPD values and the presence of BOP on day 180 were significantly associated with higher IL-1β concentrations. A strict Supra regimen reduced IL-1β concentrations over time in periodontitis patients. The benefits observed for smokers underline the importance of oral hygiene measures, even considering the presence of this important risk factor.